Enhancement of chemical stability of curcumin-enriched oil-in-water emulsions: Impact of antioxidant type and concentration. (1st August 2020) - Kharat, Mahesh; Skrzynski, Matt; Decker, Eric Andrew; McClements, David Julian
Highlights: Curcumin nanoemulsions were prepared with added antioxidants. Water soluble antioxidants could protect curcumin more effectively. Ascorbic acid concentration of ≥300 μM presented maximum curcumin protection. α-Tocopherol was the least effective in chemically protecting curcumin. Abstract: Curcumin is claimed to have many health benefits, but it has low chemical stability. In this study, the influence of food-grade antioxidants on the chemical degradation of curcumin-enriched oil-in-water emulsions was examined. The curcumin degradation rate and extent depended on antioxidant type. The water-soluble antioxidants were more effective at protecting curcumin from degradation than the oil-soluble ones, which may have been because curcumin degrades faster in water than in oil. Interestingly, the amphiphilic antioxidant was almost as effective as the water-soluble ones. The oil-soluble antioxidant actually slightly promoted curcumin degradation. In summary, curcumin retention after storage declined in the following order: 82.6% (Trolox) ~82.2% (ascorbic acid) >79.5% (ascorbyl palmitate) ≫57.9% (control) >52.7% (α-tocopherol). The effectiveness of ascorbic acid in stabilizing curcumin increased as its concentration was raised (0–300 μM). Our results may facilitate the creation of curcumin-enriched foods and beverages with enhanced bioactivity.